Case Report: Multisystem inflammatory syndrome in children with associated proximal tubular injury - Orsi, Silvia Maria; Pepino, Carlotta; Rossoni, Lisa; Serafino, Margherita; Caorsi, Roberta; Volpi, Stefano; Palmeri, Serena; Faragli, Alessandro; Lugani, Francesca; Bigatti, Carolina; Ghiggeri, Gian Marco; Verrina, Enrico Eugenio; et al. (Frontiers in Nephrology, 2023)
Introduction Sars-CoV2 infection in the pediatric population could be associated with a multiorgan inflammatory syndrome called children's multisystem inflammatory syndrome (MIS-C). Even kidneys can be affected with a broad spectrum of possible injuries, whose pathogenetic mechanisms are still unclear. Case report We report a peculiar case of a 5-year-old boy with a severe cardiac involvement in the contest of MIS-C. After two weeks, an abdominal ultrasound showed a massive bladder "debris", followed by the onset of a normoglycemic glycosuria. Over time, there was a progressive increase in glycosuria and the presence of a mat of amorphous phosphate crystals was evidenced on urinary sediment. Together with the findings of hypo-uricemia, increased urinary uric acid and globally increased urinary amino acids, a clinical picture of kidney proximal tubular damage with secondary Fanconi-like syndrome took shape. Discussion We described the case of a patient with MIS-C with cardiac and kidney involvement characterized by proximal tubular damage which slowly improved but still persists at 8 months follow-up. The pathogenesis of the damage is unclear and probably multifactorial.